Wide variation in severe neonatal morbidity among very preterm infants in European regions - Bonamy, AK (2018)
Objective To investigate the variation in severe neonatal morbidity among very preterm (VPT) infants across European regions and whether morbidity rates are higher in regions with low compared with high mortality rates. Design Area-based cohort study of all births before 32 weeks of gestational age. Setting 16 regions in 11 European countries in 2011/2012. Patients Survivors to discharge from neonatal care (n=6422). Main outcome measures Severe neonatal morbidity was defined as intraventricular haemorrhage grades III and IV, cystic periventricular leukomalacia, surgical necrotizing enterocolitis and retinopathy of prematurity grades ≥3. A secondary outcome included severe bronchopulmonary dysplasia (BPD), data available in 14 regions. Common definitions for neonatal morbidities were established before data abstraction from medical records. Regional severe neonatal morbidity rates were correlated with regional in-hospital mortality rates for live births after adjustment on maternal and neonatal characteristics. Results 10.6% of survivors had a severe neonatal morbidity without severe BPD (regional range 6.4%–23.5%) and 13.8% including severe BPD (regional range 10.0%–23.5%). Adjusted inhospital mortality was 13.7% (regional range 8.4%–18.8%). Differences between regions remained significant after consideration of maternal and neonatal characteristics (P<0.001) and severe neonatal morbidity rates were not correlated with mortality rates (P=0.50). Conclusion Severe neonatal morbidity rates for VPT survivors varied widely across European regions and were independent of mortality rates.